Densely sampled phylogenetic analyses of the Lesser Short‐toed Lark (Alaudala rufescens) — Sand Lark (A. raytal) species complex (Aves, Passeriformes) reveal cryptic diversity. (8th May 2020) - Ghorbani, Fatemeh; Aliabadian, Mansour; Zhang, Ruiying; Irestedt, Martin; Hao, Yan; Sundev, Gombobaatar; Lei, Fumin; Ma, Ming; Olsson, Urban; Alström, Per
Abstract: The taxonomy of the Lesser/Asian Short‐toed Lark Alaudala rufescens – cheleensis complex has been debated for decades, mainly because of minor morphological differentiation among the taxa within the complex, and different interpretations of the geographical pattern of morphological characters among different authors. In addition, there have been few studies based on non‐morphological traits. It has recently been suggested based on a molecular study of the lark family Alaudidae that the Sand Lark A. raytal is nested within this complex. We here analysed mitochondrial cytochrome b (cyt b ) from 130 individuals across the range of this complex (hereafter called Alaudala rufescens–raytal complex), representing all except two of the 18 currently recognized subspecies. We also analysed 11 nuclear markers from a subsample of these individuals, representing all of the clades found in the cyt b tree. Five primary clades were recovered, which confirmed that A. raytal is nested within this complex. Divergence time estimates among these five clades ranged from 1.76 to 3.16 million years (my; 95% highest posterior density [HPD] 1.0–4.51 my) or 1.99–2.53 my (95% HPD 0.96–4.3 my) in different analyses. Only four of the currently recognized subspecies were recovered as monophyletic in the cyt b tree. Our results call for a taxonomic revision, and we tentatively suggest that at least four species should be recognized, although we stress the need for an approach integrating molecular, morphological and other data that are not yet available.